2015
DOI: 10.1038/bjc.2015.222
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of the IHC4+C score in oestrogen receptor-positive early breast cancer: a prospective decision impact study

Abstract: Background:Most oestrogen receptor (ER)-positive early breast cancer diagnosed today is highly curable with multimodality treatment. Systemic adjuvant treatments including endocrine therapy and chemotherapy have made a significant contribution to the increasing cure rates over the past three decades. However not all women will require chemotherapy. The IHC4+C score is a prognostic tool that integrates four immunohistochemical measures with clinicopathological features to estimate the residual risk of distant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…Patients with low mean Ki67 could be reassured that they are likely to have a good prognosis and might be candidates for studies of reduced ADT. This study suggests that Ki67 is of maximal predictive benefit when used as a continuous variable; this method of stratification is used effectively in the clinic for Ki67 and other expression profiling-based algorithms 19 , 22 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Patients with low mean Ki67 could be reassured that they are likely to have a good prognosis and might be candidates for studies of reduced ADT. This study suggests that Ki67 is of maximal predictive benefit when used as a continuous variable; this method of stratification is used effectively in the clinic for Ki67 and other expression profiling-based algorithms 19 , 22 .…”
Section: Discussionmentioning
confidence: 93%
“…To our knowledge this is the first report using the global unweighted method in PCa. However, it is an established method to aid treatment stratification in breast cancer (19) , in which Ki67 is used clinically to distinguish between low proliferation luminal A and higher proliferative luminal B breast cancer subtypes (20) .…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used of these, Oncotype DX (by Genomic Health), is highly effective in assessing the early recurrence risk (within 5 years); however, it is less helpful in quantifying later recurrence [25,26]. Similar characteristics (with accurate assessment of the early recurrence risk but poor quantification of the later recurrence risk) have been noted with other molecular assays, including Mammaprint and the IHC4 score (summarising 4 immunohistochemical parameters) [27,28]. The Prediction Analysis of Microarray 50 (PAM50) assay and its resultant risk of recurrence (ROR) score (assessing 50 genes by quantitative polymerase chain reaction (qPCR) with subtyping of the lesions into luminal A, luminal B, human epidermal growth factor receptor 2 (HER2)-enriched and basal-like types) appears to offer more long-term predictive data with superior recurrence risk quantification in the 5-10-year range [29].…”
Section: Risk Scores For Recurrencementioning
confidence: 98%
“…Evidence from one prospective study (50) demonstrated that the IHC4 test led to changes in treatment recommendations for 34% of the patients, with 25%…”
Section: Ihc4mentioning
confidence: 99%